The impact of inflation on Sierra Leone’s current account balance - Kamara, Ishmael; Gunawan, Indra; Hirawan, Fajar (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2026)
This study examines the dynamic relationship between inflation and the current account balance (CAB) in Sierra Leone from 1980 to 2024, with a particular focus on both short-run and long-run effects. The objective is to determine the directional impact of inflation and other macroeconomic indicators on current account performance and to provide actionable insights for economic stabilization. Using the Autoregressive Distributed Lag (ARDL) bounds testing approach and Granger causality analysis, the study assesses both equilibrium and predictive relationships among inflation, the real exchange rate, foreign direct investment (FDI), GDP growth, real interest rates, and trade openness. The results indicate that, in the long run, the CAB improves by approximately 0.0867 percentage points for every one-percentage-point increase in inflation, consistent with the intertemporal current account framework. The findings also suggest feedback effects between inflation and the current account, though statistical significance varies across directions. Trade openness and FDI are found to exert negative long-run effects on the current account, while their lagged effects show positive adjustments. Exchange rate dynamics and interest rates are volatile, whereas economic growth contributes positively to the external balance. Furthermore, the results reveal that inflation Granger-causes GDP growth, real interest rates, and FDI, underscoring its broader macroeconomic influence. Overall, the findings highlight the importance of coordinated fiscal, monetary, and trade policies in maintaining external stability and macroeconomic balance in Sierra Leone.